Facebook and Virtual Democracy: A Political Movement Against the Criminalization of the KPK - Harun Ni'am (SPEKTRUM, 2010)
Abstract As a social networking website, Facebook is not only struggling in terms of companionship, but also has penetrated into the other things, including politics. Its usage has evolved from merely socializing to news of politics, fundraising, gathering masses and voicing public opinion, among others. Even Indonesian political situation recently added that as technology advances, the virtual world or the Internet, especially Facebook, should be the next pillar of democracy. Key Words : Facebook, virtual democracy, Indonesian polititical situation